Genome sequence analysis of arsenic detoxification and metabolism systems from haloarchaea isolated from high altitude andean lakes (haal) - Maldonado, Marcos Javier (2013)
HAAL are distributed across the Puna at altitudes from 4,200 to 6,000 masl. These ecosystems present extreme environmental conditions such as high levels of UV radiation, very high salt concentration (up to 4 Mor 25%), low oxygen tension, large daily temperature fluctuations ranging from 20° C during day to -40° C at night, low nutrient concentrations and the presence of heavy metals and metalloids, mainly arsenic. Among these explored lakes Antofalla and Diamante are considered the most extreme, because of the altitude and its elevated arsenic content (230 mg l-1 in Diamante; 23,000 times higher than the level regarded as safe for drinking water by the World Health Organization). Many prokaryotes, including archaea, are capable of transforming the oxidation or reduction state of metals and have the ability to derive energy in processes leading to either their solubilization or biomineralization. Arsenic is one of the most toxic environmental factors in these environments. Archaea carry genes for arsenic resistance, detoxification and metabolism. The most common system is the ars operon(arsRBCAD) composed by the ATPase (ArsA), arsenate reductase(ArsC) and an efflux pump (ArsB). Another less known system is the arsenite transporter ACR3. Other systems related to energy production from arsenic are the arr genes for the arsenate reductase that functions in anaerobic respiration, and the aso (aro,aox) genes for the arsenite oxidase that functions in aerobic resistance to arsenite.The aim of this study was to elucidate and test the genetic mechanisms of tolerance to high arsenic concentrations, taking advantage of the available genome of a strain isolated from HAAL. We studied the strains Halorubrum sp. AJ67 and Halorubrum sp. AD156, isolated from Antofalla and Diamante lakes respectively. The effect of As[V] and As[III] during growth in rich media was evaluated by different protocols. The presence of the aso, ACR3 and arr genes was assessed by degenerate oligonucleotides. PSI-BLAST and ClustalW were used to compare and align sequences, and phylogenetic trees were built using Mega5. Genome sequences were obtained using a whole-genome shotgun strategy with a 454 GS Titanium pyrosequencer at INDEAR, Argentina. Genomes were annotated and analyzed in the RAST annotation server. These isolates show enhanced resistance compared to other archaea carrying the ars operon. This could be explained by the presence of additional genes related to this function, including extra copies of the ars operon or supplementary extrusion pumps. These results suggests that the acr3, arr and aso genes in general may be more important than previously thought in environmental arsenic cycling and mobilization. Organisms with high tolerance to As, isolated in pure culture from these environments, are candidates for studies of bioremediation of metals and metalloids, a methodology of low cost and environmentally friendly.